Effects of Public Transport Improvement in the Formation of Compact Cities - Mabazza, Daniel L.; Tamura, Tohru (Journal in Urban and Regional Planning, 2014)
Many cities recently have initiated efforts in the formation and development of sustainable cities through transport policies in realizing a low carbon city. But changes in the urban structure and transport as a result of the urban growth are not sufficiently analyzed and established including its evaluation methods as a result of such changes. The study aims to evaluate the changes in urban structure and transportation in a target city-wide two million people in Japan, in an era of depopulation in the country. An empirical analysis was performed to clarify the changes in the urban structure and journey-to-work travel characteristics. In order to realize the formation of a low carbon sustainable city, an optimum commuting allocation solution was formulated by estimating reduction in the form of commuter trip length. As a result, by evaluating the changes of urban structures and transportation, estimation of the journey-to-work trip length reduction was possible. Keywords: subway, compact city, preference curve
Keywords: subway, compact city, preference curve